2014
DOI: 10.2344/0003-3006-61.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Anesthetic Management for a Patient With Klippel-Feil Syndrome

Abstract: Klippel-Feil syndrome (KFS) is a rare disease characterized by a classic triad comprising a short neck, a low posterior hairline, and restricted motion of the neck due to fused cervical vertebrae. We report repeated anesthetic management for orthognathic surgeries for a KFS patient with micrognathia. Because KFS can be associated with a number of other anomalies, we therefore performed a careful preoperative evaluation to exclude them. The patient had an extremely small mandible, significant retrognathia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Thorough cervical spine evaluation is essential to avoid potential spinal cord injury stemming from laryngoscopy, intubation, intraoperative positioning, and head manipulation that may increase the risk of craniovertebral dislocation and atlantoaxial subluxation. 8 - 10 Furthermore, proper counselling of the parents about the course, outcome, and treatment options helps to dispel the stigma surrounding this deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough cervical spine evaluation is essential to avoid potential spinal cord injury stemming from laryngoscopy, intubation, intraoperative positioning, and head manipulation that may increase the risk of craniovertebral dislocation and atlantoaxial subluxation. 8 - 10 Furthermore, proper counselling of the parents about the course, outcome, and treatment options helps to dispel the stigma surrounding this deformity.…”
Section: Discussionmentioning
confidence: 99%
“…They have cervical instability and are at high risk for spinal cord injury during laryngoscopy, intubation and positioning for surgery. 4 In 1988, Daum and Jones 5 suggested that the most prudent and effective way is an awake fibreoptic intubation. The nasal route is preferred since the tongue is out of the way and the patient cannot bite down on the tube or scope.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine instability, hypermobility, and symptomatic stenosis at the interspaces between the fused segments may develop. There have also been multiple reports of mandibular abnormalities in patients with KFS including retrognathia, 33 duplication of the mandibular rami, [34][35][36] and extra-articular ankylosis of the temporomandibular joint. 37 Progressive cervical instability or neurological compromise attributable to cervical instability is usually managed with surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine instability, hypermobility, and symptomatic stenosis at the interspaces between the fused segments may develop. There have also been multiple reports of mandibular abnormalities in patients with KFS including retrognathia, duplication of the mandibular rami, and extra-articular ankylosis of the temporomandibular joint …”
Section: Discussionmentioning
confidence: 99%